Photoinduced interfacial charge transfer processes in solar photocatalysis degradation of methylene blue using nanostructured ZnO - AL- Bawi, Zainab F. (Iraqi Journal of Physics, 2019)
In this research, design of advanced material for sunlight conversion requires focused research to obtain efficient photocatalytic system. Nanostructured ZnO was synthesized using spin coating technique. The structural, morphological and optical properties of annealed nanostructured ZnO thin film at 390 Co for 3 hours were characterized by x-ray diffraction, atomic force microscope AFM and UV-VIS spectrophotometer. Nanostructured ZnO was applied for removal Methylene Blue (MB) dye from water using sunlight induced photocatalytic process. Overall degradation of MB/ZnO was achieved after 120 minutes of sunlight irradiation while it needs more time for MB alone. The reaction rate constant fit pseudo first order for MB/ZnO degradation was 0.031 min−1 compared to 0.018 min-1 using blank sample. Annealed nanostructured ZnO thin film was considered as an excellent candidate to enhance photocatalytic system to convert sunlight to chemical energy based on interfacial charges transfer.